Further Investigation on Building and Benchmarking A Low Power Embedded Cluster for Education - Sukaridhoto, Sritrusta; Subhan Khalilullah, Achmad; Pramadihanto, Dadet (Institut Teknologi Sepuluh Nopember, 2014)
Embedded parallel computing become popular, and the future of innovation in the semiconductor industry will be in ubiquitous computing. Many researchers built embedded cluster system with limited number of devices, but we utilize the device from embedded classroom to build more number of parallel computing unit. In this paper we built low power cluster consisting 32 ARM boards with low-cost customized power supply for high performance computing class for education purpose, tested with several benchmarks on embedded cluster system and analyse the raw performance.